2010
DOI: 10.1074/jbc.m109.064790
|View full text |Cite
|
Sign up to set email alerts
|

Protein Complex of Drosophila ATRX/XNP and HP1a Is Required for the Formation of Pericentric Beta-heterochromatin in Vivo

Abstract: ATRX belongs to the family of SWI2/SNF2-like ATP-dependent nucleosome remodeling molecular motor proteins. Mutations of the human ATRX gene result in a severe genetic disorder termed X-linked ␣-thalassemia mental retardation (ATR-X) syndrome. Here we perform biochemical and genetic analyses of the Drosophila melanogaster ortholog of ATRX. The loss of function allele of the Drosophila ATRX/XNP gene is semilethal. Drosophila ATRX is expressed throughout development in two isoforms, p185 and p125. ATRX185 and ATR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
7
34
0
Order By: Relevance
“…4A, panels 2 to 5). As previously described (18)(19)(20), we also observed that animals with reduced xnp function (xnp 56 /ϩ) or lacking xnp function (xnp 56 /xnp 56 ) display derepressed w expression (Fig. 4A, panels 6 and 7).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…4A, panels 2 to 5). As previously described (18)(19)(20), we also observed that animals with reduced xnp function (xnp 56 /ϩ) or lacking xnp function (xnp 56 /xnp 56 ) display derepressed w expression (Fig. 4A, panels 6 and 7).…”
Section: Resultssupporting
confidence: 84%
“…Previous studies have shown that loss-offunction alleles of xnp affect fly viability (18)(19)(20). We similarly observed that the development of both xnp 56 /Df(3R)Exel6202 and homozygous xnp 56 embryos is affected, leading to reduced viability (Table 1).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Recombinant Proteins-Recombinant Drosophila His 6 -Su-(var)3-9 and FLAG-HP1 proteins were purified as described (40,41). Full-length Drosophila H1 and truncated H1 polypeptides were cloned into NdeI and SalI sites of pET24-iCBD vector in-frame with intein and chitin binding domain.…”
mentioning
confidence: 99%